1918 in Bildung und Erziehung Traditionen, Transitionen, Visionen - De Vincenti, Andrea; Grube, Norbert; Hoffmann-Ocon, Andreas (Historische Bildungsforschung. Tagungsbände der Sektion Historische Bildungsforschung, 2020)
"1918" signifies more than the end of the First World War. The reference to the year often also justifies narratives in the history of education. On the other hand, this volume explores the simultaneities of caesurae and traditions, ruptures and continuities in regional, national, European and global perspectives. It examines diverse paradoxes of supposedly old and new pedagogical cultures and practices as well as ambivalences of youth between rebellion and attachment to educational ideals. It also focuses on the questioning of schools and pedagogy, their relegitimisation and the intertwining of social democracy and socialism with educational reforms and traditions. In this way, the volume aims at the often described "clash of ideologies" in the interwar period and at the circulation of competing knowledge, so that it discusses the complex openness of 1918 in terms of educational history.